AIAA SPACE 2013 Conference and Exposition 2013
DOI: 10.2514/6.2013-5340
|View full text |Cite
|
Sign up to set email alerts
|

Robonaut 2 on the International Space Station: Status Update and Preparations for IVA Mobility

Abstract: Robotics engineers, ground controllers and International Space Station (ISS) crew have been running successful experiments using Robonaut 2 (R2) on-board the ISS for more than a year. This humanoid upper body robot continues to expand its list of achievements and its capabilities to safely demonstrate maintenance and servicing tasks while working alongside human crewmembers. The next phase of the ISS R2 project will transition from a stationary Intra Vehicular Activity (IVA) upper body using a power/data umbil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…The robot could then transmit this knowledge to new members of the next crew, thus providing continuity in the maintenance and transfer of knowledge. The Robonaut 2 humanoid is currently flying on the ISS [1], so such situations have a realistic future possibility.…”
Section: A Scenario For Human-robot Cooperationmentioning
confidence: 99%
See 1 more Smart Citation
“…The robot could then transmit this knowledge to new members of the next crew, thus providing continuity in the maintenance and transfer of knowledge. The Robonaut 2 humanoid is currently flying on the ISS [1], so such situations have a realistic future possibility.…”
Section: A Scenario For Human-robot Cooperationmentioning
confidence: 99%
“…Humanoid robots will play an increasingly important role in interaction with human crews in modern space-flight operations [1], and thus a major goal is to render these robots as useful as possible. Research in human social interaction has demonstrated that one of the unique abilities that provides the basis for human social interaction is cooperation [2].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, the bilateral teleoperation systems based on feedback sensory data have been widely used in various applications such as space robots [1,2], underwater robots [3], medical robots [4], emergency response robots [5], and etc. In these systems, an operator uses a human robot interface (master) at the local site to control a robot (slave) in the remote environment to execute a task.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of manipulation tasks conducted with the R2 on orbit include soft goods manipulation (blankets, wipes), switches and knobs, and tool manipulation such as RFID readers and air flow measurement tools [10]. The lessons learned from these experiments have driven the development presented in this paper.…”
Section: Introductionmentioning
confidence: 99%